Anemia hemolítica autoimune em paciente com síndrome de Kabuki - um relato de caso em São Paulo e breve discussão sobre correlação entre síndrome de Kabuki e autoimunidade - Aline Barbosa Lopes; Maki Hirose; Dário Silva Da Silva Júnior (Sociedade Brasileira de Pediatria, 2022)
Kabuki syndrome (KS), first described in Japan in 1981, is a rare disease characterized by a peculiar facies, postnatal growth de?ciency, intellectual disability and a set of malformations, such as skeletal and visceral abnormalities. In the natural history of KS, abnormal immune events are presents and this case report contribute with the understanding and consolidation of hematologic autoimmune desorders. This article describes a case report of a patient with previous diagnosis of Kabuki syndrome with a autoimmune hemolytic anemia in a hospital of São Paulo, with adequate response and resolution with corticosteroids terapy. The article also makes as a brief explanation of correlation with autoimmunity, immunodeficiency and Kabuki syndrome.